Aspectos macroscópicos e microscópicos de lesões cutâneas e pulmonares em Tapirus terrestris (Tapiridae) associadas a incêndios florestais no Pantanal Mato-Grossense - Barcenas Olaya, Camilo Eduardo (2024)
Forest fires are relatively common in Brazil and bring as one of the consequences, risks to the health of animals living in the affected areas. In 2020, numerous fires destroyed vast areas of the wetland, affecting thousands of animals, including the tapir (Tapirus terrestris), a species of high biological value cataloged as vulnerable by the International Union for Conservation of Nature (IUCN). Between September and November 2020, 12 tapirs rescued with skin burns and appendages were sent to the Veterinary Hospital of the Federal University of Mato Grosso. Of these, 11 died and one survived. All of them were submitted to evaluation of the extent and depth of the burns on the skin and appendages. All those who died were submitted to necropsy and samples were collected for morphological and microbiological evaluation. The area of skin burns ranged from 2.3% to 26.15% and was classified between Deep grade II and IV. Foot lesions were observed in 11 tapirs, and the corneal case fell in eight. Bacterial pneumonia occurred in seven tapirs. It was found that foot injuries in limb joints or that cause the corneal case to fall, restricting movement, compromise the survival of this species. Dermal lesions predispose to bacterial pneumonia that further reduces the chances of survival of tapirs victims of forest fires.